Hadith #2764 - Sunan Abi Dawud - al-Miswar bin Makhrama bin Nawfal; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
A woman would give security from the believers and it would be allowed.
Grade: Sahih

Hadith #2963 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله (Sunan Abi Dawud)
‘Umar sent for me when the day rose high. I found him sitting on a couch without cover. When I entered upon him, he said: Malik, some people of you tribe gradually came here, and I have ordered to give them something, so distribute it among them. I said: If you assigned this (work) to some other person, (it would be better). He said: Take it. Then Yarfa’ came to him and said: Commander of the Faithful, will you permit ‘Uthman b. ‘Affan, ‘Abd al-Rahman b. ‘Awf, al-Zubair b. al-‘Awwa
Grade: Sahih

Hadith #3438 - Sunan Abi Dawud - Abdullah bin Tawus عبد الله بن طاوس; ibn Abbas; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
The Prophet (ﷺ) forbade to bid against one another.
Grade: Sahih

Hadith #4100 - Sunan Abi Dawud - Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله; Safiyya bint Shayba bin 'Uthman; Umm Salamah (Sunan Abi Dawud)
When Surat an-Nur came down, they took the curtains, tore them and made head covers (veils) of them.
Grade: Hasan

Hadith #4106 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hisham bin 'Urwa هشام بن عروة; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The Prophet (ﷺ) brought Fatimah a slave which he donated to her. Fatimah wore a garment which, when she covered her head, did not reach her feet, and when she covered her feet by it, that garment did not reach her head. When the Prophet (ﷺ) saw her struggle, he said: There is no harm to you: Here is only your father and slave.
Grade: Sahih

Hadith #4653 - Sunan Abi Dawud - al-Miswar bin Makhrama bin Nawfal; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
No one of those who took the oath of allegiance under the tree will go to hell.
Grade: Sahih

Hadith #4681 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amir bin Sa'd ibn Abi Waqqas عامر بن سعد بن أبي وقاص; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله; Sa'd ibn Abi Waqqas (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone loves for Allah’s sake, hates for Allah’s sake, gives for Allah’s sake and withholds for Allah’s sake, he will have perfect faith.
Grade: Sahih